Meningkatkan Motivasi dan Loyalitas Karyawan UMKM Enaxmen Boga Rasa Semarang dengan Program Kemitraan - Masine Slahanti; Nisa Novia Avien Christy; Enggar Dhian Pratamanti (BADAN PENERBIT STIEPARI PRESS, 2025)
MSMEs play a role in improving the welfare of the wider community, as well as improving the national economy. In the Indonesian economy, MSMEs are the business group with the largest number and have been proven to be able to withstand various kinds of economic crisis shocks. The development of MSMEs receives support from various parties, where the government and elements of society help develop and improve MSMEs so that people who own these businesses can improve their economy, and academics also contribute by providing or holding activities, counseling and training aimed at increasing success and improving the economy for business owners. One of the MSMEs in Semarang is engaged in milkfish processing. The owner, Mrs. Kurniawati, has a milkfish processing business with the brand